So we read on : how The Great Gatsby came to be and why it endures - Corrigan, Maureen (New York : Little, Brown and Company, 2014)
"The 'Fresh Air' book critic investigates the enduring power of The Great Gatsby -- 'The Great American Novel we all think we've read, but really haven't.' Conceived nearly a century ago by a man who died believing himself a failure, it's now a revered classic and a rite of passage in the reading lives of millions. But how well do we really know The Great Gatsby? As Maureen Corrigan, Gatsby lover extraordinaire, points out, while Fitzgerald's masterpiece may be one of the most popular novels in America, many of us first read it when we were too young to fully comprehend its power. Offering a fresh perspective on what makes Gatsby great--and utterly unusual--So We Read On takes us into archives, high school classrooms, and even out onto the Long Island Sound to explore the novel's hidden depths, a journey whose revelations include Gatsby's surprising debt to hard-boiled crime fiction, its rocky path to recognition as a 'classic, ' and its profound commentaries on the national themes of race, class, and gender. With rigor, wit, and infectious enthusiasm, Corrigan inspires us to re-experience the greatness of Gatsby and cuts to the heart of why we are, as a culture, 'borne back ceaselessly' into its thrall. Along the way, she spins a new and fascinating story of her own"--Publisher information.
Water, water, everywhere -- "In the land of ambition and success" -- Rhapsody in noir -- A second-rate, Midwest hack and the masterpiece he wrote -- Here lies one whose name was writ in water -- I didn't get it the first time.
Includes bibliographical references (pages 327-333) and index.
Keywords: Fitzgerald, F. Scott -- 1896-1940.; Great Gatsby (Fitzgerald, F. Scott); Fitzgerald, F. Scott -- 1896-1940; Fitzgerald, F. Scott -- 1896-1940.; LITERARY CRITICISM -- Books & Reading; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- Ancient & Classical; United States; Literature, American -- Criticism; NonFiction; Literary; Narrative non-fiction.